Fiber Optic Hydrophones for towed array applications. (January 2023) - Bruno, F.A.; Janneh, M.; Gunda, A.; Kyselica, R.; Stajanca, P.; Werzinger, S.; Gruca, G.; Rijnveld, N.; Persiano, G.V.; Cutolo, A.; Pisco, M.; Cusano, A.
Highlights: A fiber optic hydrophone was designed and developed. Performance characterizations were carried out in an instrumented tank. A towed array with five hydrophone was demonstrated. Abstract: In this paper, we report the design and development of a fiber optic hydrophone for underwater applications. The sensing configuration is based on a Michelson interferometer where a fiber coil is wrapped around a compliant mandrel acting as a sensitive element. The acoustic wave leads to a deformation of the mandrel that is transferred into strain in the optical fiber. Two Fiber Bragg gratings are used at the terminal ends of the fiber coil to enable the fiber elongation measurement. A similar "dummy" hydrophone is used as reference. The sensor was designed to be sensitive to sea state zero. The fabricated hydrophones were characterized in an instrumented tank. An acoustic source was used to generate acoustic tones in the frequency range 3 ÷ 25 kHz. A reference piezoelectric hydrophone was used to record the underwater acoustic waves in the tank. The hydrophone exhibited a responsivity of about 19 nm/Pa in the frequency range 3 ÷ 10 kHz allowing a resolution of 0.3 mPa/Hz 1/2 . The linearity and directivity of the sensors were carefully investigated. The fiber optic hydrophone was used as a basic building block to conceive and fabricated a towed array with five elements. The multiplexed hydrophones in the towed array were simultaneously interrogated and the responsivity of the hydrophones were retrieved. Beyond the good repeatability in terms of hydrophone responsivity, the tests in the tank confirm the capability of the fiber optic technology to offer technological solutions for underwater operation with potential advantages in terms of lightness and small-size for use in unmanned underwater vehicles.